From metaphysics to the philosophy of religion. José Gómez Caffarena's intellectual itinerary - Fraijó, Manuel (Razón y fe, 2018)
There have not been many among the Spanish philosophers and theologians who lucidly and hopefully passed from metaphysics to religion. One of the first, perhaps the first and, until now, the only one, was the recently deceased Jesuit José Gómez Caffarena. In this article, after a meaningful biographical note, its author offers us the reasons why Caffarena naturally went from the science of questions - metaphysics - to the answers that the philosophy of religion - the Christian religion - offered and continue to offer today. An answer in which the enigma and the mystery still stand, accompanied, of course, by the hope of the one who knows himself to be the victor of evil.